Formation and Propagation of Tau Oligomeric Seeds - Gerson, Julia E.; Kayed, Rakez (Frontiers in Neurology, 2013)
Tau misfolding and aggregation leads to the formation of neurofibrillary tangles (NFTs), which have long been considered one of the main pathological hallmarks for numerous neurodegenerative diseases known as tauopathies, including Alzheimer’s Disease (AD) and Parkinson’s Disease (PD). However, recent studies completed both in vitro and in vivo suggest that intermediate forms of tau, known as tau oligomers, between the monomeric form and NFTs are the true toxic species in disease and the best targets for anti-tau therapies. However, the exact mechanism by which the spread of pathology occurs is unknown. Evidence suggests that tau oligomers may act as templates for the misfolding of native tau, thereby seeding the spread of the toxic forms of the protein. Recently, researchers have reported the ability of tau oligomers to enter and exit cells, propagating from disease-affected regions to unaffected areas. While the mechanism by which the spreading of misfolded tau occurs has yet to be elucidated, there are a few different models which have been proposed, including cell membrane stress and pore-formation, endocytosis and exocytosis, and non-traditional secretion of protein not enclosed by a membrane. Coming to an understanding of how toxic tau species seed and spread through the brain will be crucial to finding effective treatments for neurodegenerative tauopathies.